“Komedi within Komedi”: Moving Pictures and Intermedial Crossings in Turn-of-the-Century Colonial Indonesia - Ruppin, Dafna (Archīum Ateneo, 2024)
In the past thirty years studies of early cinema, mostly focusing on the history of film production and exhibition in the West, have been preoccupied with examining the emergence of moving images within their intermedial sphere. The case of moving picture exhibition and consumption in turn-of-the-century colonial Indonesia, with its rich selection of itinerant indigenous and Western amusements on offer, thus presents an especially intriguing case. This article situates itself within this transnational stream of commercial entertainments, known in Malay by the generic term komedi. In the process, it examines stories adapted across different media and cultural contexts, which were consumed by local audiences of various ethnicities and social standing in colonial society, specifically highlighting the conditions that led to an exceptional 1906 local film production of the popular folklore story of Nyai Dasima. While no known footage from this production survives, this paper proposes an intermedial reconstruction by looking at surviving traces of the text in other turn-of-the-century media forms. By exploring the re-incarnations of Nyai Dasima, alongside other popular stories shared across media platforms in colonial Indonesia, the article fleshes out how early entrepreneurs of moving pictures were utilizing intermedial connections in order to embed the new medium within the local media landscape. Conversely, by drawing on contemporary newspaper reports in Dutch and Malay, this article aims to show that local spectators made sense of the new medium of moving pictures through negotiations with and in relation to established entertainment forms they were habituated in.